HUBUNGAN ANTARA ASUPAN KAFEIN, KUALITAS TIDUR DAN STATUS GIZI DENGAN TEKANAN DARAH - Khoerunisa, Sarah; Hermanto, Restu Amalia; Aminarista, Aminarista (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: approximately 9.4% of men and 8.9% of women in developing countries aged 20-24 years experience high blood pressure. In Indonesia the incidence of high blood pressure in the age group over 18 years is 25.8%. Blood pressure in students can be influenced by caffeine intake, sleep quality and nutritional status. Objective: This study aims to determine the relationship between caffeine intake, sleep quality and nutritional status with blood pressure. Method: This research was conducted at STT Wastukancana students using cross sectional research design and 82 subjects were selected by simple random sampling. Caffeine intake was measured using a semi-quantitative food frequency Questionnaire (SQ-FFQ), sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, nutritional status was measured using Body Mass Index (BMI), blood pressure was measured using a digital sphygnomanometer. The relationship of each independent variable with systolic blood pressure was tested using Pearson product momment, whereas the relationship between the independent variable and diastolic blood pressure was tested using the Spearman rank. Multivariate test used multiple linear regression test. Results: Most subjects had high systolic blood pressure (61%) and high diastolic blood pressure (74.4%). Caffeine intake, sleep quality and nutritional status each have a relationship with systolic blood pressure and diastolic blood pressure. Factors associated with increased systolic blood pressure were caffeine intake (B = 0.12; p = 0.004), sleep quality (B = 1.36; p = 0.001) and nutritional status (B = 1.25; p = 0.001). Poor sleep quality of the subjects in this study can be caused by disturbances both before falling asleep or during sleep. Conclusion: High blood pressure is influenced by caffeine intake, sleep quality and nutritional status.